Personal Spaces and Communal Consequences: Navigating Geographical Tensions With the Socially Responsible Behavior through Embodied Thinking (SORBET) Project - Lim, Kenneth Y. T.; Li, Samuel C. X. (Frontiers in Virtual Reality, 2022)
The coronavirus pandemic has impacted societies in different ways. This variation is inherently geographical, with patterns across space and time reflecting underlying societal inequalities. This paper describes a learning intervention designed to afford participants opportunities to experience the diffusion of a (virtual) virus within a community, albeit in a safe way. The intervention was enacted in March 2021 among nine undergraduate teachers-in-training at a teacher-education institute in Singapore. Participants were invited to reflect on the connections between their personal decision-making and its impact on the broader community, after having first undertaken a collaborative task in a virtual environment. The Socially Responsible Behaviour through Embodied Thinking (SORBET) Project draws on the learning sciences in terms of embodied cognition and projective identity, and in this paper, seeks to apply them to geographical understandings of diffusion. Responses from post-activity interviews are reported along three themes, as structured by Cultural-Historical Activity Theory. Through encouraging reflection on authentic experience, the authors hope to catalyse a more grounded appreciation of the need to practise positive social habits in the context of a pandemic and, by extension, contribute to the fight against the virus through the application of geographical thinking at scales local and global.